Metal phosphide modified lithium-rich manganese-based positive electrode material as well as preparation method and application thereof

By introducing metal phosphides into lithium-rich manganese-based positive electrode materials and synergistically stabilize the oxygen structure, the problems of voltage hysteresis, capacity/voltage attenuation and limited cycle life in lithium-ion batteries are solved, and high energy density and long cycle life are achieved Take into account both.

CN119481043AActive Publication Date: 2025-02-18ZHEJIANG UNIV +1

Patent Information

Application Number
CN202411694545.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-18
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

Lithium-rich manganese-based positive electrode materials have problems such as voltage hysteresis, capacity/voltage attenuation and limited cycle life in lithium-ion batteries, making it difficult to take into account high energy density and long cycle life.

Method used

By introducing metal phosphides, especially iron phosphide, manganese phosphide and molybdenum phosphide, lithium-rich manganese-based positive electrode materials are modified, and the oxygen structure is stabilized, the oxygen peroxidation and transition metal migration are prevented, and the crystal structure of the material is improved. Stability and electrochemical properties.

Benefits of technology

The excellent cycle stability and rate performance of lithium-rich manganese-based positive electrode material was achieved, and the capacity did not decrease significantly after 800 cycles, which significantly improved the energy density and cycle stability of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481043A_ABST
    Figure CN119481043A_ABST
Patent Text Reader

Abstract

The invention discloses a metal phosphide modified lithium-rich manganese-based positive electrode material and a preparation method and application thereof, the lithium-rich manganese-based positive electrode material comprises a metal phosphide and a lithium-rich manganese positive electrode base material, the metal phosphide is doped in the lithium-rich manganese positive electrode base material, or the surface of the lithium-rich manganese positive electrode base material is modified. The lithium-rich manganese-based positive electrode material has excellent cycling stability and rate capability, and the capacity is not obviously reduced after 800 times of cycling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-ion batteries, and in particular to a metal phosphide-modified lithium-rich manganese-based positive electrode material and a preparation method and application thereof. Background Art

[0002] The development of high-performance, low-cost new cathode materials has always been a hot topic and focus in the field of lithium-ion battery research. Compared with lithium cobalt oxide, lithium iron phosphate and high-nickel ternary cathode materials, lithium-rich manganese-based cathode materials xLiMO2·(1-x)Li2MnO3 are expected to become the cathode materials for the next generation of commercial high-energy lithium-ion batteries due to their high specific capacity, low price and good thermal stability. However, lithium-rich manganese-based cathode materials for lithium-ion batteries have serious voltage hysteresis and capacity / voltage decay, resulting in limited cycle life, which needs to be improved urgently.

[0003] At present, researchers at home and abroad have studied the O 2- The failure mechanisms of overoxidation, phase structure evolution, lattice displacement / strain, etc. were investigated, and a variety of modification methods were designed and developed, including ion doping, surface modification, pre-lithiation, morphology regulation, ion exchange, chemical composition and defect structure design, etc., to effectively improve the electrochemical performance of lithium-rich manganese cathode materials. Although researchers have gradually deepened their understanding of lithium-rich manganese-based cathode materials for lithium-ion batteries and made significant improvements, the voltage decay and performance degradation caused by the irreversible redox of oxygen in the materials still pose challenges to their industrial application.

[0004] The invention patent with publication number CN118281208A discloses a lithium-rich manganese-based positive electrode material, including a substrate and a coating layer. The chemical formula of the substrate is mLi2MnO3·(1-m)LiTMO2, where 0<m≤0.5, TM is one or more of Ni, Co, Mn, V, and Al, and the coating layer includes Li 3-x M 0.05 BS3, x is 0.05 or 0.1 or 0.2 or 0.25, M is at least one of Cu, Zn, Sn, P. The lithium-rich manganese-based positive electrode material is double-modified by doping and coating to improve the structural reversibility of the positive electrode material and the initial coulombic efficiency of the battery. However, the capacity of the modified material remains at ~90% after 100 cycles, and the cycle stability needs to be further improved.

[0005] In the invention patent with publication number CN118507698A, NaMF4 is used to coat the lithium-rich manganese-based positive electrode material, where M is one or more of Co, Sc, and Y. The coating protects the lithium-rich manganese material from being corroded by the electrolyte, and at the same time inhibits the decomposition of the electrolyte, thereby improving the electrochemical performance of the battery. However, the preparation method is a hydrothermal method and a liquid phase coating method, which needs to be optimized to achieve the simple preparation of high-performance lithium-rich manganese-based positive electrode materials.

[0006] Therefore, there is an urgent need for an efficient method for preparing lithium-rich manganese-based positive electrode materials to solve the current problem that high energy density and long cycle life of positive electrode materials cannot be taken into account at the same time, and to achieve breakthroughs in the energy density, cycle stability and rate performance of lithium-ion batteries. Summary of the invention

[0007] The present invention provides a metal phosphide modified lithium-rich manganese-based positive electrode material, which has excellent cycle stability and rate performance, and has no obvious capacity decrease after 800 cycles.

[0008] The present invention provides a lithium-rich manganese-based positive electrode material modified by a metal phosphide. The lithium-rich manganese-based positive electrode material comprises a metal phosphide and a lithium-rich manganese positive electrode substrate. The metal phosphide is doped in the lithium-rich manganese positive electrode substrate, or the surface of the lithium-rich manganese positive electrode substrate is modified.

[0009] Preferably, the metal phosphide is selected from one or more of iron phosphide, nickel phosphide, cobalt phosphide, manganese phosphide, molybdenum phosphide, copper phosphide, titanium phosphide, zinc phosphide, chromium phosphide, vanadium phosphide, scandium phosphide, lithium phosphide, aluminum phosphide, ruthenium phosphide, sodium phosphide and potassium phosphide.

[0010] The present invention utilizes phosphorus anions and metal cations to collaboratively stabilize the oxygen structure of the lithium-rich manganese positive electrode substrate. Phosphorus anions can act as a redox pair, improve the charge distribution in the crystal, regulate the distribution of oxygen ions and the localized electronic structure, increase the migration energy barrier of lattice oxygen, and reduce the reactivity of lattice oxygen; metal cations further enhance the bonding strength between oxygen and lattice metal, collaboratively prevent oxygen peroxidation and the migration of transition metal ions, inhibit oxygen release under high voltage and the irreversible phase transition from layered structure to spinel or rock salt phase, and enhance the stability of the crystal structure of the material. In addition, phosphorus anions and metal cations work together at the interface to reduce side reactions between the electrolyte and the lithium-rich manganese-based material, optimize the migration channel of lithium ions, and enhance the lithium ion diffusion rate and conductivity.

[0011] Further preferably, the metal phosphide is selected from one or more of iron phosphide, manganese phosphide and molybdenum phosphide.

[0012] The iron cations and phosphorus anions in iron phosphide have multiple valence states, forming an electronic coupling effect with transition metals (such as Mn and Ni) during the charge and discharge process, alleviating lattice stress strain and enhancing the stability of the oxygen structure. In addition, the chemical stability and low interface impedance of iron phosphide can stabilize the electrode / electrolyte interface and improve interface compatibility.

[0013] The introduction of manganese phosphide can adjust the coordination environment of manganese in lithium-rich manganese materials, reduce the breakage of Mn-O bonds and the tendency of oxygen release through phosphating, and maintain the integrity of the layered structure. The high conductivity of manganese phosphide helps to form an electron transfer network in the positive electrode material, while optimizing the diffusion path of lithium ions and improving the rate performance and overall conductivity of the material.

[0014] The surface of molybdenum phosphide has highly active sites that can promote the kinetics of redox reactions. The high-valent molybdenum ions in molybdenum phosphide can compensate for the charge balance during the charging and discharging process of lithium-rich manganese-based materials and prevent oxygen peroxidation. Molybdenum phosphide has high conductivity and a unique electronic structure. It improves the electronic conductivity of lithium-rich manganese positive electrode materials through electronic coupling, optimizes the lithium ion migration path, and reduces the polarization effect during the charging and discharging process.

[0015] Iron phosphide, manganese phosphide and molybdenum phosphide all have high chemical stability and electronic conductivity, and can maintain their structural integrity within a high voltage range. At the same time, they form chemical bonds with the lithium-rich manganese matrix to stabilize the oxygen structure, effectively improving the electronic conductivity of the lithium-rich manganese cathode. In addition, a stable protective layer can be formed at the interface of the lithium-rich manganese material, effectively inhibiting electrolyte decomposition and side reactions.

[0016] Further preferably, the metal phosphide is molybdenum phosphide, and the mass percentage of the molybdenum phosphide in the lithium-rich manganese-based positive electrode material is 0.01-0.03%.

[0017] Molybdenum phosphide has the best effect in lithium-rich manganese-based cathode materials due to its chemical stability, high conductivity, redox activity and interface protection ability. Molybdenum phosphide has high chemical and thermal stability and can maintain stability under high voltage (~4.8V) and multiple cycle conditions; the phosphorus and molybdenum elements in molybdenum phosphide easily form strong covalent bonds with the oxygen atoms of lithium-rich manganese cathode materials, significantly enhancing the stability of oxygen and reducing oxygen release; the redox pair of molybdenum (Mo 3+ / Mo 6+ ) and the multi-electron pairs of phosphorus anions can effectively compensate for the charge balance, slow down the structural stress during the change of transition metal oxidation state, and maintain structural stability; the high electronic conductivity and interface stability of molybdenum phosphide can effectively improve the electron and ion transport properties of lithium-rich manganese positive electrode materials, inhibit the dissolution of transition metal ions, and enhance the interface compatibility of lithium-rich manganese materials.

[0018] At a content of 0.01-0.03%, molybdenum phosphide can be evenly distributed in lithium-rich manganese-based materials without destroying the crystal structure of the material itself. Excessive addition of molybdenum phosphide may cause local distortion of the crystal structure of lithium-rich manganese materials, increase lattice stress, and reduce electrochemical performance. When too much molybdenum phosphide is added, an excessively thick molybdenum phosphide protective layer and impurities, such as molybdenum oxide or phosphate compounds, may be formed on the surface of the lithium-rich manganese positive electrode, hindering the diffusion and migration of lithium ions, producing additional side reactions, and leading to poor electrochemical performance. An appropriate content of molybdenum phosphide can significantly improve the overall conductivity of lithium-rich manganese positive electrode materials and effectively stabilize the oxygen structure on the surface without excessively changing the intrinsic properties of the material. Within this range, the addition of molybdenum phosphide is moderate, which can fully exert the synergistic modification effect of molybdenum and phosphorus elements without causing negative effects such as ion channel blockage, lattice distortion or secondary phase generation. Therefore, at an appropriate content, the electrochemical performance of the material is maximized.

[0019] Preferably, the mass percentage of the metal phosphide in the lithium-rich manganese-based positive electrode material is 0.01-10%.

[0020] If the content is too low (<0.01%), the oxygen structure stability and electrochemical properties of lithium-rich manganese materials cannot be significantly improved, the conductivity and interface compatibility are limited, and the material performance improvement is not obvious. If the content is too high (>10%), the metal phosphide will introduce a secondary phase or interface side reaction, destroy the stability of the crystal structure, hinder the migration of lithium ions, increase the interface impedance, and reduce the rate performance and energy density. When the content is in the range of 0.01-10%, the metal phosphide can be evenly distributed, significantly improving oxygen stability, conductivity and interface compatibility, while avoiding too many side effects. This range achieves the best balance between performance improvement and material economy.

[0021] Preferably, the general structural formula of the lithium-manganese-rich positive electrode substrate is xLi2MnO3-(1-x)LiMO2; wherein M is selected from one or more of Ni, Co, Mn, Ti, Cr, Fe, Al, Nb, Mo, and Ru, and 0≤x≤1.

[0022] On the other hand, the present invention also provides a method for preparing the metal phosphide modified lithium-rich manganese-based positive electrode material, comprising:

[0023] The lithium-rich manganese positive electrode substrate precursor is pyrolyzed and then mixed evenly with the metal phosphide, and calcined at high temperature to obtain the metal phosphide-doped lithium-rich manganese-based positive electrode material;

[0024] Alternatively, the lithium-rich manganese positive electrode substrate, metal phosphide, conductive agent, binder and solvent are uniformly mixed to form a slurry, the slurry is coated on a current collector, and after drying, the lithium-rich manganese-based positive electrode material with the metal phosphide surface modified is prepared.

[0025] The preparation process of the lithium-rich manganese-based positive electrode material provided by the present invention is simple and efficient, and is expected to realize the commercial application of high-capacity lithium-rich manganese-based materials.

[0026] The preparation method of the metal phosphide modified lithium-rich manganese-based positive electrode material disclosed in the present invention is a conventional mixing and coating method in the art. The positive electrode material is obtained in one step by introducing the metal phosphide during the calcination process of the lithium-rich manganese-based positive electrode material or the electrode preparation process. The method is simple, the material preparation is highly controllable, and it is suitable for industrial production.

[0027] In the process of preparing the metal phosphide-doped lithium-rich manganese-based positive electrode material, the present invention:

[0028] Preferably, the method for preparing the lithium-rich manganese positive electrode substrate precursor includes a spray drying method, a coprecipitation method, a sol-gel method, a combustion method, a solid phase method or a molten salt method.

[0029] Further preferably, the lithium-rich manganese positive electrode substrate precursor prepared by spray drying comprises the following steps:

[0030] The raw materials are prepared according to the molar percentage of each component of the lithium-rich manganese positive electrode substrate, and then added into deionized water to form a mixed solution, a complexing agent is added into the mixed solution, and the mixture is stirred to obtain a metal salt precursor solution;

[0031] The metal salt precursor solution is sprayed, dried and ground by a spray drying method to obtain a lithium-rich manganese positive electrode substrate precursor.

[0032] The present invention utilizes a spray drying method to mix the raw materials in a liquid, and compared with the existing solid mixing, the Li element distribution in the prepared lithium-rich manganese positive electrode substrate precursor can be more uniform.

[0033] Further preferably, the raw material is acetate, nitrate, sulfate, carbonate, oxalate or metal oxide.

[0034] More preferably, the raw material is acetate.

[0035] Acetates (such as manganese acetate, nickel acetate, etc.) have good solubility in water or organic solvents, and can form a uniform precursor solution to ensure uniform distribution of ions during atomization, avoid agglomeration between metal ions, and have consistent particle composition; acetates have a low melting point and can be decomposed into metal oxides at a lower temperature, making the calcination stage after spray drying easier to control; acetate solutions have low viscosity, can evaporate evenly, have strong surface tension, and are easy to form regular particles. The obtained precursor with good packing density can optimize the reaction efficiency of subsequent calcination; the decomposition products of acetates are relatively simple, and it is not easy to generate byproducts that are difficult to remove (such as sulfates that may have residual sulfate), which reduces the impact on subsequent battery performance; acetates have high purity, sulfates may introduce residual sulfates, and chlorides produce corrosive chloride ions. The products released by acetates during decomposition (such as CO2 and H2O) are harmless to the environment. As an industrial chemical, acetates are widely available and moderately priced, making them more suitable for large-scale production.

[0036] Preferably, the pyrolysis temperature is 200-700° C., and the heat treatment time is 0.5-8 hours.

[0037] Preferably, the method of uniformly mixing the lithium-rich manganese cathode substrate precursor with the metal phosphide after pyrolysis includes grinding, ball milling, mechanical stirring or magnetic stirring.

[0038] Preferably, the calcination atmosphere is air, oxygen or vacuum, the calcination temperature is 600-1100° C., and the treatment time is 2-24 hours.

[0039] Preferably, the lithium-rich manganese positive electrode material is selected from the cobalt-free lithium-rich manganese positive electrode material 0.5Li2MnO3-0.5LiNi 0.5 Mn 0.5 O2.

[0040] Preferably, the metal phosphide is selected from one or more of iron phosphide, manganese phosphide and molybdenum phosphide.

[0041] In the process of preparing the lithium-rich manganese-based positive electrode material with metal phosphide surface modification, the present invention:

[0042] Preferably, the lithium-rich manganese positive electrode material is selected from the cobalt-free lithium-rich manganese positive electrode material 0.5Li2MnO3-0.5LiNi 0.5 Mn 0.5 O2.

[0043] Preferably, the metal phosphide is selected from one or more of iron phosphide, manganese phosphide and molybdenum phosphide.

[0044] Preferably, the conductive agent is selected from one or more of graphite, acetylene black, Super P, carbon nanotubes, graphene, and Ketjen black.

[0045] Preferably, the binder is selected from one or more of vinylidene fluoride, polytetrafluoroethylene, polyacrylonitrile, styrene-butadiene rubber, sodium carboxymethyl cellulose and sodium alginate.

[0046] Preferably, the current collector is one or more of aluminum foil, carbon-coated aluminum foil, and nickel foil.

[0047] Preferably, the solvent is selected from water or a mixed solvent consisting of water and an organic solvent, and is adaptively selected according to the type of binder used.

[0048] Furthermore, the binder is selected from sodium carboxymethyl cellulose, and the solvent is selected from water.

[0049] On the other hand, the present invention also provides the use of a metal phosphide-modified lithium-rich manganese-based positive electrode material in a lithium-ion battery, including:

[0050] A lithium-ion battery is obtained by assembling a positive electrode sheet prepared with the lithium-rich manganese-based positive electrode material modified by the metal phosphide, a negative electrode and an electrolyte.

[0051] Preferably, the negative electrode is a graphite carbon negative electrode, a silicon-based negative electrode, a metal oxide negative electrode or a lithium metal negative electrode.

[0052] Preferably, the electrolyte also adopts an organic electrolyte commonly used in the art, including a lithium salt and an organic solvent, wherein the lithium salt is one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), and lithium bistrifluoromethylsulfonyl imide (LiTFSI); the organic solvent is one or more of dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC), and vinylene carbonate (VC).

[0053] Compared with the prior art, the present invention has the following beneficial effects:

[0054] The present invention regulates the bulk structure or surface interface structure of the lithium-rich manganese-based positive electrode material by introducing metal phosphides, and the metal cations and phosphorus anions jointly stabilize the oxygen structure of the lithium-rich manganese material, prevent oxygen peroxidation and migration of transition metals, improve the crystal structure stability of the material, and effectively improve the capacity retention rate, voltage retention rate and rate performance of the lithium-rich manganese-based positive electrode material during long charge and discharge cycles. The lithium-ion battery assembled with the lithium-rich manganese-based positive electrode material cycles 800 times at a current density of 1C (1C = 200mA / g) without obvious capacity loss. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 The charge-discharge and cycle performance curves of the battery assembled in Example 1 of the present invention, wherein: Figure 1 (a) is the first charge and discharge curve; Figure 1(b) is the 0.1C cycle performance curve; Figure 1 (c) is the 1C cycle performance curve;

[0056] Figure 2 A curve diagram of the discharge median voltage of the battery assembled in Example 1 of the present invention during the cycle process;

[0057] Figure 3 This is a graph showing the energy density cycle curve of the positive electrode active material of the assembled battery of Example 1 of the present invention;

[0058] Figure 4 The first charge and discharge curve of the battery assembled in Example 2 of the present invention at a current density of 0.1C (20mA / g);

[0059] Figure 5 The cycle performance curve of the battery assembled in Example 2 of the present invention at a current density of 1C (200 mA / g);

[0060] Figure 6 The cycle performance curve of the battery assembled in Example 4 of the present invention at a current density of 1C (200 mA / g);

[0061] Figure 7 The cycle performance curve of the battery assembled in Example 5 of the present invention at a current density of 1C (200 mA / g);

[0062] Figure 8 The cycle performance curve of the battery assembled in Example 7 of the present invention at a current density of 1C (200 mA / g);

[0063] Fig. 9 The cycle performance curve of the battery assembled in Example 8 of the present invention at a current density of 1C (200 mA / g);

[0064] Fig.10 The cycle performance curve of the battery assembled in Example 9 of the present invention at a current density of 1C (200 mA / g);

[0065] Fig.11 The cycle performance curve of the battery assembled in Example 11 of the present invention at a current density of 1C (200 mA / g);

[0066] Fig.12 The cycle performance curve of the battery assembled in Example 12 of the present invention at a current density of 1C (200 mA / g);

[0067] Fig.13 The cycle performance curve of the battery assembled in Comparative Example 1 of the present invention at a current density of 1C (200 mA / g);

[0068] Fig.14 This is a cycle performance curve diagram of the battery assembled in Comparative Example 2 of the present invention at a current density of 1C (200 mA / g). DETAILED DESCRIPTION

[0069] The present invention is further described below with reference to the examples, but the scope of the present invention is not limited thereto. The materials involved in the examples are all commercially available products.

[0070] Example 1

[0071] (1) Lithium-rich manganese-based positive electrode materials were prepared by spray drying combined with high-temperature solid-phase sintering. Specifically, 29.19 g of CH3COOLi·2H2O (99.9%), 11.19 g of Ni(CH3COO)2·4H2O (99.9%) and 33.08 g of Mn(CH3COO)2·4H2O (99.9%) were weighed according to the molar ratio of Li:Ni:Mn=1.272:0.2:0.6, and added to 1.5 L of deionized water to form 0.15 mol L -1 Then add 94.56 g of C6H8O7·H2O (99.5%, 0.3 mol L -1 ) as a complexing agent, and a transparent metal salt precursor solution was obtained by mechanical stirring combined with ultrasonic treatment for 10 minutes. The reaction solution was then sent to the nozzle of the spray dryer by a peristaltic pump to obtain a spray-dried precursor material. The peristaltic pump speed was set to 15 rpm, the inlet temperature was set to 230°C, and the outlet temperature was set to 100°C. The spray-dried precursor was collected, ground, and placed in an alumina crucible, which was then placed in a muffle furnace and heat treated at 900°C for 10 hours in an air atmosphere, with a heating rate of 3°C min -1 , and Li is obtained by cooling in the furnace 1.2 Mn 0.6 Ni 0.2 O2 positive electrode material.

[0072] Weigh Li according to the mass ratio of 8:1 1.2 Mn 0.6 Ni 0.2 O2 and conductive agent Super P, add 3wt% Mn3P2 (accounting for Li 1.2 Mn 0.6 Ni 0.2The mixture was mixed evenly with 1wt% of carboxymethyl cellulose (CMC) in a mass ratio of 90:5, and then mixed by ultrasonic dispersion for 30 minutes to form a uniform slurry. The slurry was then coated on an aluminum foil current collector cleaned with hydrochloric acid and anhydrous ethanol, and dried in vacuum at 110°C for 12 hours. After compaction at a pressure of 10 MPa, a 3wt% Mn3P2 surface-modified lithium-rich manganese positive electrode sheet was obtained, which was recorded as 3wt% Mn3P2-Li 1.2 Mn 0.6 Ni 0.2 O2.

[0073] The electrochemical performance of the positive electrode prepared in this example was characterized by using a Cr2025 button cell. 1.2 Mn 0.6 Ni 0.2 The O2 positive electrode sheet was cut into 10 mm electrode sheets, weighed, and placed in a vacuum oven at 110°C to remove moisture from the electrode surface. The electrode was then assembled in a glove box filled with argon (water and oxygen content were both less than 0.1 ppm). A metal lithium sheet was used as the counter electrode, the diaphragm was Celgard-2400, and the electrolyte was LiPF6 (1 mol L -1 ) EC / DEC / EMC (volume ratio of 1:1:1) solution. The active material loading of all electrodes was 2.0±0.5mg cm -2 The electrochemical performance of button cells was tested by constant current charge and discharge, with a test voltage range of 2.0-4.8V.

[0074] Example 2-3

[0075] The preparation process of the lithium-rich manganese positive electrode sheet and the assembly test conditions of the button cell of Example 2-3 are the same as those of Example 1. The difference from Example 1 is that Li is weighed at a mass ratio of 8:1. 1.2 Mn 0.6 Ni 0.2 O2 powder and conductive agent Super P were added with 5wt% and 1wt% Mn3P2, respectively, to obtain 1wt% Mn3P2 and 5wt% Mn3P2 surface-modified lithium-rich manganese positive electrodes, respectively recorded as 5wt% Mn3P2-Li 1.2 Mn 0.6 Ni 0.2 O2 and 1wt% Mn3P2-Li 1.2 Mn 0.6 Ni 0.2 O2.

[0076] Example 4

[0077] The preparation process of the lithium-rich manganese positive electrode sheet and the assembly test conditions of the button cell of Example 2-3 are the same as those of Example 1. The difference from Example 1 is that Li is weighed at a mass ratio of 8:1. 1.2 Mn 0.6 Ni 0.2 O2 powder and conductive agent Super P were added with 4wt% Fe3P to obtain a 4wt% Fe3P surface modified lithium-rich manganese positive electrode sheet, denoted as 4wt% Fe3P-Li 1.2 Mn 0.6 Ni 0.2 O2.

[0078] Embodiment 5-7

[0079] The preparation process of the lithium-rich manganese positive electrode sheet and the assembly test conditions of the button cell of Example 5-7 are the same as those of Example 1. The difference from Example 1 is that Li is weighed at a mass ratio of 8:1. 1.2 Mn 0.6 Ni 0.2 O2 powder and conductive agent Super P were added with 3wt%, 2wt%, and 1wt% Fe3P, respectively, to obtain Fe3P surface modified lithium-rich manganese positive electrode sheets, which were recorded as 3wt%Fe3P-Li 1.2 Mn 0.6 Ni 0.2 O2, 2wt%Fe3P-Li 1.2 Mn 0.6 Ni 0.2 O2 and 1wt%Fe3P-Li 1.2 Mn 0.6 Ni 0.2 O2.

[0080] Example 8

[0081] The preparation process of the spray-dried lithium-rich manganese precursor and the assembly test conditions of the button cell in Example 8 are the same as those in Example 1. The difference from Example 1 is that the spray-dried lithium-rich manganese precursor is heated at 3°C ​​min -1 The temperature was raised to 500 °C and calcined for 5 h. After cooling in the furnace, the mixture was ground and mixed with MoP according to the ratio of Ni:Mn:MoP=0.2:0.6:0.005. The resulting mixture was placed in a muffle furnace under air atmosphere at 3 °C min -1 The temperature was raised to 900 °C and calcined for 10 h, and then cooled and ground to obtain MoP-doped Li 1.2 Mn 0.6 Ni 0.2 O2 positive electrode material, denoted as Li 1.2 Mn 0.6 Ni 0.2 O2-0.005MoP.

[0082] Examples 9-10

[0083] The preparation process of the spray-dried lithium-rich manganese precursor and the assembly test conditions of the button cell of Example 9-10 are the same as those of Example 1. The difference from Example 1 is that the spray-dried lithium-rich manganese precursor is heated at 3°C ​​min -1 The mixture was heated to 500 °C and calcined for 5 h. After cooling in the furnace, it was ground and mixed with MoP according to the molar ratio of Ni:Mn:MoP of 0.2:0.6:0.01 and 0.2:0.6:0.03 respectively. The obtained mixture was placed in a muffle furnace under air atmosphere at 3 °C min -1 The temperature was raised to 900 °C and calcined for 10 h, and then cooled and ground to obtain MoP-doped Li 1.2 Mn 0.6 Ni 0.2 O2 positive electrode materials, respectively denoted as Li 1.2 Mn 0.6 Ni 0.2 O2-0.01MoP and Li 1.2 Mn 0.6 Ni 0.2 O2-0.03MoP.

[0084] Embodiment 11

[0085] Example 11 Preparation process of lithium-rich manganese spray-dried precursor and assembly test conditions of button cells are the same as those in Example 1. The difference from Example 1 is that the spray-dried lithium-rich manganese precursor is heated at 3°C ​​min -1 The temperature was raised to 500℃ and calcined for 5h. After cooling in the furnace, the mixture was ground and mixed with Fe3P according to Ni:Mn:Fe3P=0.2:0.6:0.005. The mixture was placed in a muffle furnace under air atmosphere at 3℃min -1 The temperature was raised to 900℃ and calcined for 10h, and then ground during furnace cooling to obtain Fe3P-doped Li 1.2 Mn 0.6 Ni 0.2 O2 positive electrode material, denoted as Li 1.2 Mn 0.6 Ni 0.2 O2-0.005Fe3P.

[0086] Examples 12-13

[0087] The preparation process of the spray-dried lithium-rich manganese precursor and the assembly test conditions of the button cell of Example 9-10 are the same as those of Example 1. The difference from Example 1 is that the spray-dried lithium-rich manganese precursor is heated at 3°C ​​min -1The mixture was heated to 500 °C and calcined for 5 h. After cooling in the furnace, it was ground and mixed with Fe3P according to the molar ratio of Ni:Mn:Fe3P of 0.2:0.6:0.01 and 0.2:0.6:0.03 respectively. The obtained mixture was placed in a muffle furnace under air atmosphere at 3 °C min -1 The temperature was raised to 900℃ and calcined for 10h, and then ground during furnace cooling to obtain Fe3P-doped Li 1.2 Mn 0.6 Ni 0.2 O2 positive electrode materials, respectively denoted as Li 1.2 Mn 0.6 Ni 0.2 O2-0.01Fe3P and Li 1.2 Mn 0.6 Ni 0.2 O2-0.03Fe3P.

[0088] Comparative Example 1

[0089] Comparative Example 1 Spray drying of lithium-rich manganese precursor is the same as in Example 1, except that the lithium-rich manganese precursor is placed in a muffle furnace under air atmosphere at 3°C ​​min -1 Heat to 900℃ and calcine for 10h, then grind to obtain Li 1.2 Mn 0.6 Ni 0.2 O2 cathode material,

[0090] Comparative Example 2

[0091] Comparative Example 2: Spray-dried lithium-rich manganese precursor is the same as Example 1, except that the spray-dried lithium-rich manganese precursor is heated at 3 °C min -1 Heat to 500℃ and calcine for 5h. After cooling in the furnace, grind and place in a muffle furnace under air atmosphere at 3℃min -1 Heat to 900℃ and calcine for 10h, then grind to obtain Li 1.2 Mn 0.6 Ni 0.2 O2 positive electrode material.

[0092] like Figure 1 As shown, Figure 1In the figure, (a) is the first charge and discharge curve of the battery assembled in Example 1 at a current density of 0.1C (20mA / g), with the first discharge specific capacity as high as 290mAh / g and the first coulombic efficiency of 82%. (b) is the rate performance curve of the battery assembled in Example 1, which has a high discharge specific capacity at 0.1C, 0.5C, 1C, 2C, 5C and 10C. It can still release specific capacities of 175mA / g and 146mAh / g at high rates of 5C and 10C, respectively, showing excellent rate performance. (c) is the cycle performance curve of the battery assembled in Example 1 at a current density of 1C (200mA / g). During the cycle process, the discharge specific capacity increases slowly in the initial stage, and can still release a specific capacity of 207mAh / g after about 400 cycles, with a capacity retention rate of 97%, showing excellent cycle stability.

[0093] Figure 2 This is the discharge median voltage curve during the cycle of the battery assembled in Example 1. The results show that the discharge median voltage of the material in this example is 2.98V after 400 cycles, and the retention rate is 85%. Figure 3 This is the energy density cycle curve of the positive electrode active material of the battery assembled in Example 1. After 400 cycles, the energy density of the active material is 649Wh / kg, and the retention rate is 86%, showing good voltage retention and energy density retention rate.

[0094] Figure 4 This is the first charge and discharge curve of the battery assembled in Example 2 at a current density of 0.1C (20mA / g), and the first discharge specific capacity is 261mAh / g. Figure 5 The cycle performance curve of the battery assembled in Example 2 at a current density of 1C (200 mA / g) is shown. During the cycle, the discharge capacity increases slowly in the initial stage, and after 400 cycles, it can still release a capacity of 208 mAh / g, with a capacity retention rate of 87%, showing good cycle stability.

[0095] Figure 6 The cycle performance curve of the battery assembled in Example 4 at a current density of 1C (200 mA / g) shows that after 450 cycles, it can still release a specific capacity of 188 mAh / g, and the capacity retention rate is 91%, showing good cycle stability.

[0096] Figure 7 The cycle performance curve of the battery assembled in Example 5 at a current density of 1C (200 mA / g). During the cycle, the discharge capacity increases slowly in the initial stage, and after 450 cycles, it can still release a capacity of 155 mAh / g, with a capacity retention rate of 85%, indicating that the introduction of the metal phosphide ratio affects the cycle stability. Figure 7The cycle performance curve of the battery assembled in Example 5 at a current density of 1C (200 mA / g). During the cycle, the discharge capacity increases slowly in the initial stage, and after 450 cycles, it can still release a capacity of 155 mAh / g, with a capacity retention rate of 85%, indicating that the introduction of the metal phosphide ratio affects the cycle stability.

[0097] Figure 8 The cycle performance curve of the battery assembled in Example 7 at a current density of 1C (200 mA / g) shows that after 450 cycles, it can still release a specific capacity of 171 mAh / g, with a capacity retention rate of 92%, showing good cycle stability.

[0098] Fig. 9 The cycling performance curve of the battery assembled in Example 8 at a current density of 1C (200mA / g). During the cycling process, the discharge capacity increases slowly in the initial stage, and after 800 cycles, it can still release a capacity of 180mAh / g, with no obvious capacity decay, showing excellent cycling stability.

[0099] Fig.10 The cycling performance curve of the battery assembled in Example 9 at a current density of 1C (200mA / g). During the cycling process, the discharge capacity increased slowly in the initial stage, and after 800 cycles, it could still release a capacity of 176mAh / g, with no obvious capacity decay, showing excellent cycling stability.

[0100] Fig.11 The cycle performance curve of the battery assembled in Example 11 at a current density of 1C (200mA / g). During the cycle, the discharge capacity increased slowly in the initial stage, and after 450 cycles, it could still release a capacity of 179mAh / g, with a capacity retention rate of 98%, showing excellent cycle stability.

[0101] Fig.12 The cycling performance curve of the battery assembled in 12 embodiments at a current density of 1C (200mA / g). During the cycling process, the discharge capacity increases slowly in the initial stage, and after 450 cycles, it can still release a capacity of 152mAh / g, with a capacity retention rate of 86%, indicating that the introduction of the metal phosphide ratio affects the cycling stability.

[0102] Fig.13 The cycling performance curve of the battery assembled in Comparative Example 1 at a current density of 1C (200 mA / g) is shown. The discharge specific capacity decays rapidly during the recycling process, and the discharge specific capacity is close to zero after 450 cycles.

[0103] Fig.14The cycle performance curve of the battery assembled in Comparative Example 2 at a current density of 1C (200 mA / g). During the cycle, the capacity gradually decayed, and after 700 cycles, a specific capacity of 92 mAh / g was released, and the capacity retention rate was 50%, indicating that the lithium-rich manganese-based material without the addition of metal phosphide has poor cycle stability.

Claims

1. A metal phosphide-modified lithium-rich manganese-based positive electrode material, characterized in that: The lithium-rich manganese-based positive electrode material comprises a metal phosphide and a lithium-rich manganese positive electrode substrate, wherein the metal phosphide is doped in the lithium-rich manganese positive electrode substrate, or the surface of the lithium-rich manganese positive electrode substrate is modified.

2. The metal phosphide-modified lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The metal phosphide is selected from one or more of iron phosphide, nickel phosphide, cobalt phosphide, manganese phosphide, molybdenum phosphide, copper phosphide, titanium phosphide, zinc phosphide, chromium phosphide, vanadium phosphide, scandium phosphide, lithium phosphide, aluminum phosphide, ruthenium phosphide, sodium phosphide and potassium phosphide.

3. The metal phosphide-modified lithium-rich manganese-based positive electrode material according to claim 2, characterized in that: The metal phosphide is selected from one or more of iron phosphide, manganese phosphide and molybdenum phosphide.

4. The metal phosphide-modified lithium-rich manganese-based positive electrode material according to claim 3, characterized in that: The metal phosphide is molybdenum phosphide, and the mass percentage of the molybdenum phosphide in the lithium-rich manganese-based positive electrode material is 0.01-0.03%.

5. The metal phosphide-modified lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The mass percentage of the metal phosphide in the lithium-rich manganese-based positive electrode material is 0.01-10%.

6. The metal phosphide-modified lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The general structural formula of the lithium-manganese-rich positive electrode substrate is xLi2MnO3-(1-x)LiMO2; wherein M is selected from one or more of Ni, Co, Mn, Ti, Cr, Fe, Al, Nb, Mo, and Ru, and 0≤x≤1.

7. A method for preparing a metal phosphide-modified lithium-rich manganese-based positive electrode material according to any one of claims 1 to 6, characterized in that: include: The lithium-rich manganese positive electrode substrate precursor is pyrolyzed and then mixed evenly with the metal phosphide, and calcined at high temperature to obtain the metal phosphide-doped lithium-rich manganese-based positive electrode material; Alternatively, the lithium-rich manganese positive electrode substrate, metal phosphide, conductive agent, binder and solvent are uniformly mixed to form a slurry, the slurry is coated on a current collector, and after drying, the lithium-rich manganese-based positive electrode material with the metal phosphide surface modified is prepared.

8. The method for preparing a phosphide-modified lithium-rich manganese-based positive electrode material according to claim 7, characterized in that: The lithium-rich manganese positive electrode substrate precursor prepared by spray drying comprises the following steps: The raw materials are prepared according to the molar percentage of each component of the lithium-rich manganese positive electrode substrate, and then added into deionized water to form a mixed solution, a complexing agent is added into the mixed solution, and the mixture is stirred to obtain a metal salt precursor solution; The metal salt precursor solution is sprayed, dried and ground by a spray drying method to obtain a lithium-rich manganese positive electrode substrate precursor.

9. The method for preparing a phosphide-modified lithium-rich manganese-based positive electrode material according to claim 8, characterized in that: The raw material is acetate, nitrate, sulfate, carbonate, oxalate or metal oxide.

10. Use of the metal phosphide-modified lithium-rich manganese-based positive electrode material according to any one of claims 1 to 6 in a lithium-ion battery, characterized in that: include: A lithium-ion battery is obtained by assembling a positive electrode sheet prepared with the lithium-rich manganese-based positive electrode material modified by the metal phosphide, a negative electrode and an electrolyte.

Citation Information

Patent Citations

  • Lithium-rich manganese-based positive electrode material as well as preparation method and application thereof

    CN118281208A

  • Coated and modified lithium-rich manganese-based positive electrode material as well as preparation method and application thereof

    CN118507698A

  • Modification method of lithium-rich cathode material

    CN102969495A

  • Spinel nickel manganese acid lithium and layered lithium-rich manganese-based composite cathode material with core-shell structure and preparation method thereof

    CN104157831A

  • Preparation method for lithium-rich manganese-based positive electrode material coated by phosphate polyanion composite manganese salt

    CN106058221A

Cited By

  • Lithium-rich manganese-based positive electrode material with in-situ surface regulation and control, and preparation method and application of lithium-rich manganese-based positive electrode material

    CN120300169A